Learning for Sustainability in Times of Accelerating Change - Wals, Arjen E. J.; Corcoran, Peter Blaze (The Netherlands : Wageningen Academic Pub., 2012)
'We live in turbulent times, our world is changing at accelerating speed. Information is everywhere, but wisdom appears in short supply when trying to address key inter-related challenges of our time such as; runaway climate change, the loss of biodiversity, the depletion of natural resources, the on-going homogenization of culture, and rising inequity. Living in such times has implications for education and learning. This book explores the possibilities of designing and facilitating learning-based change and transitions towards sustainability. In 31 chapters contributors from across the world discuss (re)emerging forms of learning that not only assist in breaking down unsustainable routines, forms of governance, production and consumption, but also can help create ones that are more sustainable. The book has been divided into three parts: re-orienting science and society, re-connecting people and planet and re-imagining education and learning. This is essential reading for educators, educational designers, change agents, researchers, students, policymakers and entrepreneurs alike, who are concerned about the well-being of the planet and convinced of our ability to do better.'--pub. desc.
Chapter 7 Queering ecology: interrogating'seductions to organic wholeness' in popular environmental rhetoric / Joseph P. Weakland -- Chapter 8 Building resilient communities: where disaster management and facilitating innovation meet / Karen Elisabeth Engel and Paul Gerard Hendrik Engel -- Chapter 9 Towards successful joint knowledge production for global change and sustainability: lessons from six Dutch adaptation projects / Dries Hegger, Annemarie van Zeijl-Rozema and Carel Dieperink -- Chapter 10 Getting active at the interface: how can sustainability researchers stimulate social learning? / Jayne H. Glass, Alister Scott and Martin F. Price -- PART TWO -- RE-CONNECTING PEOPLE AND PLANET -- Chapter 11 Finding hope in a world of environmental catastrophe / Elin Kelsey and Carly Armstrong -- Chapter 12 Inviting the unforeseen: a dialogue about art, learning and sustainability / Natalia Eernstman, Jan van Boeckel, Shelley Sacks and Misha Myers -- Chapter 13 Relationship-based experiential learning in practical outdoor tasks / Erling Krogh and Linda Jolly -- Chapter 14 Transformative learning: towards the social imaginary of sustainability: learning from indigenous cultures of the American continent / Sylvia Catharina van Dijk and Eduardo Ernesto van Dijk -- Chapter 15 Re-connecting with traditional knowledge: the experience of the Shangri-la institute for sustainable communities in China / Yunhua Liu and Alicia Constable
Includes bibliographical references.
Keywords: Environmental education; Sustainable development; Environmental sciences -- Study and teaching